Ulasan Live Streaming Penjualan Produk: Analisis Bahasa Persuasif Host Dalam Bisnis Digital - Ester Anieon Parapat; Arshita Adelia; Aqilah Keisya; Widya Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Live streaming has become a dominant digital marketing strategy in Indonesia's ecommerce ecosystem. This study analyzes the use of persuasive language by live streaming hosts in influencing consumer purchasing decisions. Using a qualitative approach with content analysis methods, this study examines the persuasive language techniques used by popular hosts on the TikTok Shop platform. The results show that the effectiveness of hosts' persuasive language greatly depends on a combination of word choice, tone of voice, and the ability to build emotional interactions with the audience. Theoretically, this study enriches the applied linguistics literature in the context of digital business. Practically, these findings serve as strategic guidelines for ecommerce businesses in optimizing their marketing strategies.